Systematic Literature Review: Determinants of Financial Statement Disclosure in Local Governments and Implications for Jambi City Government - Mery Rohaya Sihombing; Sri Rahayu; Rico Wijaya (International Journal of Economic and Business Research, 2026)
Financial statement disclosure is a critical element of public sector accountability and transparency, yet the determinants influencing disclosure quality in local governments remain fragmented across the literature. This study aims to systematically review and synthesize the determinants of local government financial statement disclosure and to derive implications for the Jambi City Government. Using a Systematic Literature Review (SLR) approach, relevant studies were identified from major academic databases and analyzed through thematic synthesis and qualitative content analysis. The findings indicate that disclosure quality is influenced by interconnected factors, including human resource competence, governance quality, internal control systems, audit mechanisms, organizational commitment, information systems, and accounting standards implementation. The review also reveals growing attention to technological and organizational dimensions alongside traditional governance and compliance factors. The synthesis suggests that effective disclosure practices require integrated institutional, managerial, and technological support rather than reliance on regulatory compliance alone. The study contributes by providing a comprehensive framework of disclosure determinants and offering evidence-based insights for strengthening financial transparency and accountability in local governments.